Liberalism in the Development of Non-Formal Education - Safitri, Winda; Jamaris, Jamaris; Setiawati, Setiawati (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
This paper aims to discuss liberalism in the development of non-formal education. Liberalism is a part that can develop non-formal education. Indeed individualism, rsionalism, freedom and responsibility are the ideals championed by liberalism, although in real practice the ideal values referred to by liberalism have not been fully realized. Non-formal education is education whose implementation is outside the formal channels that have flexibility in its implementation, therefore liberalism is an understanding that emphasizes freedom but still within the limits of reasonable freedom that is still bound by rules. In the implementation of non-formal education, liberalism is very good to apply where citizens can freely determine what they need without being bound by the system or rules. So it should be in non-formal education that this liberalism is used so that learning citizens can freely make their choicesKeywords: Liberalism, Non-Formal Education